Religion for realists: why we all need the scientific study of religion - Perry, Samuel L. (Oxford University Press, 2024)
"Religion matters. It shapes the personal lives of the vast majority of human beings on the planet and there's evidence its influence over global politics is growing, not shrinking. Yet we in the Western world often misunderstand much about how religion functions. Influenced by dominant Anglo Protestant culture, when we think about "religion" we tend to think about individual beliefs, doctrines, and the transformative power of individual religious actors. On the contrary, the best social science teaches us religion's importance and power lie more in the deep culture of social norms and identity, the imperatives of human populations, and the rules and resources of social structure"--